1993
DOI: 10.1093/brain/116.4.903
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of multiple memory systems in the human brain

Abstract: Patients with global amnesia of different aetiologies (n = 11), and patients with probable Alzheimer's disease of recent onset and mild to moderate severity (n = 18) underwent extensive neuropsychological examination, which included the evaluation of multiple components of memory, and a measurement of regional cerebral glucose metabolism with [18F]fluoro-deoxyglucose ([18F]FDG) and PET. In the neuropsychological tests, both global amnesia and Alzheimer's disease patients had impaired episodic long-term memory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
63
0
4

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(82 citation statements)
references
References 0 publications
15
63
0
4
Order By: Relevance
“…As described, medial temporal regions are a major source of projections to the medial parietal͞ posterior cingulate, and their disruption leads to medial parietal͞posterior cingulate hypometabolism in both humans and animals (18,(20)(21)(22)(23)(24). The DAT-related activation in the current study might thus reflect a loss of regulation or functional inhibition.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…As described, medial temporal regions are a major source of projections to the medial parietal͞ posterior cingulate, and their disruption leads to medial parietal͞posterior cingulate hypometabolism in both humans and animals (18,(20)(21)(22)(23)(24). The DAT-related activation in the current study might thus reflect a loss of regulation or functional inhibition.…”
Section: Discussionmentioning
confidence: 54%
“…Studies in both animals and humans show that lesions including the entorhinal and perirhinal cortex lead to reduced posterior cingulate resting metabolism similar to that seen in DAT (20)(21)(22)(23)(24). It has been suggested that posterior cortical regions, in particular, the posterior cingulate and precuneus, may be involved in memory function, and that DATrelated hypometabolism may ref lect memory impairment (25)(26)(27)(28)(29).…”
mentioning
confidence: 91%
“…Nevertheless, studies from neuropsychology and experimental psychology have produced enough evidence for several neurally and functionally dissociable memory systems that this hypothesis must be taken seriously (e.g., Campbell & Conway, 1995;Cohen, 1984;Foster & Jelicic, 1999;Hodges, Spatt, & Patterson, 1999;R. Johnson, Kreiter, Zhu, & Russo, 1998;Knowlton, Mangels, & Squire, 1996;Markowitsch et al, 1993;Markowitsch, Calabrese, Neufeld, Gehlen, & Durwen, 1999;McCarthy & Warrington, 1990;McClelland et al, 1995;Perani et al, 1993;Peretz, 1996;Reber, Knowlton, & Squire, 1996;Schacter & Tulving, 1994;Shallice, 1979;Squire, 1987Squire, , 1992Tulving, 1983Tulving, , 1985Tulving, , 1987Tulving, , 1993aTulving & Schacter, 1990;Van der Linden, Bredart, Depoorter, & Coyette, 1996;Vargha-Khadem et al, 1997;Warrington, 1975;Weiskrantz, 1987Weiskrantz, , 1990.…”
Section: Multiple Systems Multiple Functionsmentioning
confidence: 99%
“…Voxel-based mapping of the correlations between memory performance and resting regional metabolic rates of glucose measured by positron emission tomography (PET) has been demonstrated to be a sensitive approach to delineate the neural substrates of cognitive impairment in patients with frontal lobe lesions (Reed, Lasseron, Marsden, Bright, Stanhope & Kopelman, 2005), and in degenerative diseases such as Alzheimer's disease (see for example, Perani, Bressi, Cappa, Vallar, Alberoni, Grassi et al, 1993;Desgranges, Baron, Lalevée, Giffard, Viader, de la Sayette et al, 2002;Desgranges, Baron, Giffard, Chételat, Lalevée, Viader et al, 2002;Eustache, Desgranges, Giffard, de la Sayette & Baron, 2001;Rauchs, Piolino, Mézenge, Landeau, Lalevée, Pélerin, et al, 2006), more precisely to enlighten the neural basis of AM deficits in Alzheimer's disease . In the present study, we used PET and statistical parametric mapping (SPM) to map the correlations between resting-state FDGUptake in the whole brain and scores reflecting AM in a group of fv-FTD patients.…”
Section: Introductionmentioning
confidence: 99%